Income Analysis of Duck Farming Business in Maccini Baji Village, Lau District, Maros Regency - Masir, Ummul; Nadia, Aisyah Ainun; Aisyah, Aisyah (Journal Gallus Gallus, 2024)
Duck farming is one of the livestock commodities developed by the community as a source of income because the rearing system is easy to reach. This research aims to determine the income of duck breeders in Maccini Baji Village, Lau District, Maros Regency. The population used was 54 farmers with purposive sampling based on the following criteria: 1) Livestock ownership between 20 and 100 animals; 2) The farmers had applied intensive or semi-intensive rearing systems; and 3) Have at least one year of farming experience. From the total population, 40 farmers were categorized as respondents based on the research criteria. Data is processed using cost analysis by calculating total costs (TC), revenues (R), and income (I). The results depict that the average TC is Rp. 19,213,100; The average R is IDR. 28,655,250, and (I) Rp. 9,442,150. In sum, duck farming in Maccini Baji Village is profitable for two months because the income exceeds the costs incurred.